The impact of racial diversity of executive managers on financial performance of South African state-owned companies - Hlobo, M. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
Globally, companies are increasingly embracing both gender and racial diversity and are beginning to witness the impact of this diversity on performance. Several studies suggest that with increased diversity, companies can gain access to unique networks, information and human capital, which ultimately improves financial performance. In this paper, we investigate whether racial diversity at executive management level bears financial benefits. The study is set in the South African context where, since the advent of democracy in 1994, regulations such as the Employment Equity Act of 1998 require companies to racially diversify their workforce. This study examines data from 21 state-owned companies (SOCs), covering the period of 2010 to 2014. Correlation and regression analysis was used to examine the relationship between the racial composition of executive managers (Black, White, Indian or Coloured) and the companies' financial performance (i.e. profit margin, return on assets and fruitless and wasteful expenditure as a percentage of revenue). The results indicate that there is slow progress made by the South African government on including non-whites in their executive management teams in SOCs. However, no correlation was found between the racial diversity of the management teams and the financial performance of these SOCs. These findings are significant, particularly for South African regulators and policy makers, as they provide justification for increased efforts to racially diversify the South African executive management teams in SOCs. This is important since numerous studies have demonstrated that such diversity is financially beneficial, particularly in the private sector. Keywords: Financial performance, State-owned companies, Racial diversity, Workforce
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Financial performance; State-owned companies; Racial diversity; Workforce; Government business enterprises; Ethnopsychology